Sosialisasi Pencegahan Penyebaran Virus Corona Melalui Video Edukasi : Peran Mahasiswa Sastra Inggris Unkhair Dalam Mengahadapi New Normal - Sulmi Magfirah (LPPM Universitas Bumigora, 2021)
Socialization of the prevention of the Corona virus through videos in the New Normal era aims (1) to provide the information to the public and knowledge about preventing the spread of the Coronavirus, starting from wearing a mask, washing hands, social distance, safe from Coronavirus transmission, maintaining immunity and (2)to provide an education to the society in preventing the spread of the Coronavirus in the New Normal era. In producing the video itself, it was carried out several stages, including; making a timeline for socialization activities and a video script. The next step is taking videos such as; Taking Videos of some students who will do the socialization, taking videos to appeal the prevention of COVID-19 in the New Normal era by the Head of English Literature Study Program at the Faculty of Cultural Sciences. The next is video editing, which will be merging and editing the videos that have been taken. The last is publishing through several social media, including Facebook, Instagram, and Whatsapp, and on DVD for internal production of the Faculty of Cultural Sciences Khairun University.